Social network position predicts male mating success in a small passerine. (28th May 2021) - Beck, Kristina B; Farine, Damien R; Kempenaers, Bart
Abstract: Individuals differ in the quantity and quality of their associations with conspecifics. The resulting variation in the positions that individuals occupy within their social environment can affect several aspects of life history, including reproduction. While research increasingly shows how social factors can predict dyadic mating patterns (who will breed with whom), much less is known about how an individual's social position affects its overall likelihood to acquire mating partner(s). We studied social networks of socially monogamous blue tits ( Cyanistes caeruleus ) to investigate whether the number and strength of connections to opposite-sex conspecifics, the ratio between same- and opposite-sex connections, and the tendency to move between social groups in the months prior to breeding affect individuals' success in acquiring 1) a breeding partner and 2) an extrapair partner. After controlling for differences in spatial location, we show that males that moved more often between social groups were more likely to acquire a breeding partner. Moreover, adult males that associated with more females were more likely to sire extrapair young. The number of female associates also predicted the proportion of familiar female breeding neighbors, suggesting that familiarity among neighbors may facilitate opportunities for extrapair matings. In females, none of the network metrics significantly predicted the likelihood of acquiring a breeding or extrapair partner. Our study suggests that the positioning of males within their social environment prior to breeding can translate into future mating success, adding an important new dimension to studies of (extrapair) mating behavior. Abstract : Differences in individual sociality can have important fitness consequences. Using social network analysis, we test whether differences in individual social position affect the overall likelihood of an individual to acquire mating partners in blue tits. We show that males that moved more often between social groups were more likely to acquire a breeding partner. Further, adult males that associated with more females were more likely to sire extrapair young.